Comparative in-vitro activity of ceftaroline against Staphylococcus aureus isolates from India - Bakthavatchalam, Yamuna Devi; Pragasam, Agila Kumari; Anandan, Shalini; Joshi, Sangeetha; Chaudhuri, Bhaskar Naryanan; Chitnis, DS; Roy, Indranil; Tapan, Dhole; Veeraraghavan, Balaji (The Journal of Infection in Developing Countries, 2016)
This item has no abstract. Follow the links below to access the full text.